Heterogeneity in Outcome Reporting in Endoscopic Endonasal Skull Base Reconstruction: A Systematic Review - Dorismond, Christina; Santarelli, Griffin D.; Thorp, Brian D.; Kimple, Adam J.; Ebert, Charles S., Jr.; Zanation, Adam M. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective Presently, there are no standards for reporting outcomes of endoscopic endonasal skull base reconstruction (ESBR). This is problematic as a lack of consistent reporting makes synthesizing findings in systematic reviews and meta-analysis challenging. Thus, the aim of this study was to systematically review and describe the patterns of reporting outcomes in ESBR as a foundation for developing reporting guidelines.Study Design Present study is a systematic review.Methods Embase, PubMed, CINAHL, Cochrane Library, and Web of Science were searched for all publications with ≥25 patients and a focus on ESBR. The reporting patterns of each study's variables and outcomes were assessed.Results A total of 112 studies were included in the review. The most commonly reported demographic variables were the number of included patients (n = 112, 100%) and types of pathologies treated (n = 104, 92.9%). Meanwhile, the most routinely described preoperative variable was history of prior treatment (n = 48, 42.9%). Type of reconstruction was a commonly reported intraoperative variable (n = 110, 98.2%), though the rate of intraoperative cerebrospinal fluid (CSF) leak was noted in only 76 studies (67.9%). With regard to postoperative outcomes, postoperative CSF leak rate was routinely provided (n = 101, 90.2%), but reporting of other surgical complications was more inconsistent. Ultimately, of the 43 variables and outcomes reviewed, a median of 12 (range: 4–22) was reported in each study.Conclusion There is significant heterogeneity in the outcomes reported in studies relating to ESBR. This highlights the need for the development of standard reporting guidelines to minimize bias and improve interstudy comparability.
Keywords: endoscopic endonasal approach; skull base surgery; skull base reconstruction; systematic review; outcome reporting